Application of Imaging Techniques to Cases of Drug-Induced Crystal Nephropathy in Preclinical Studies. (27th February 2017) - Lenz, Barbara; Brink, Andreas; Siam, Monira; De Paepe, Anne; Bassett, Simon; Eichinger-Chapelon, Anne; Maliver, Pierre; Neff, Rachel; Niederhauser, Urs; Steinhuber, Bernd; Zurbach, Raphael; Singer, Thomas; et al.
Abstract: A number of drugs can cause precipitates within renal tubules leading to crystal nephropathy. Crystal nephropathy is usually an exposure-related finding and is not uncommon in preclinical studies, where high doses are tested. An understanding of the nature of precipitates is important for human risk assessment and further development. Our aim was to investigate the ability of various imaging techniques to detect the presence of drugs or metabolites in renal crystals. We applied matrix-assisted laser desorption/ionization—Fourier transform ion cyclotron resonance mass spectrometry (MALDI-FTICR MS) imaging, Raman and infrared microspectroscopy, scanning electron microscopy coupled with energy dispersive X-ray (SEM/EDX) spectroscopy and standard histopathology to cases of drug-induced crystal nephropathy, induced in rodents and primates by 4 compounds. MALDI-FTICR MS imaging enabled the identification of the drug-related crystal content in all 4 cases of nephropathy, without reference material and with high accuracy. Crystals were composed of unchanged parent drug and/or metabolites. Similar results were obtained using Raman and infrared microspectroscopy for 2 compounds. In the absence of reference standards of metabolites, Raman and infrared microspectroscopy showed that the crystals consisted of components similar, but not identical, to the administered drug for the other compounds, a limitation for these techniques. SEM/EDX showed which counter ions were colocalized with the identified drug-related material, complementing the MALDI-FTICR MS findings. Therefore, we recommend MALDI-FTICR MS as a first-line methodology to characterize crystal nephropathies. Raman and infrared microspectroscopy may be useful when MALDI-FTICR MS imaging cannot be applied. SEM/EDX could be considered as a complementary technology.